GOOD DESIGN AND MANUFACTURE TO GET A GOOD RELIABILITY OF RENEWABLE ENERGY POWER PLANT - Guntur Pratama Putra; Erry Rimawan (Universitas Mercu Buana, 2017)
Easier access to the global marketplace today makes local product competition with products from the global market increasing, pushing designers better to make machines as efficient as possible while still paying attention to their reliability. In obtaining good reliability, from the design stage of the machine and its manufacture must have root cause analysis that can help to guide design and manufacturing processes. However, for renewable energy fields, it is very difficult to build from the beginning as raw materials come from overseas acquired in the global market. In the domestic raw material is processed creatively to gain added value of the product and make it a superior product that is installed and marketed locally. Photovoltaic monitoring will independently keep the grid stable and conceptual able to monitor the health of every photovoltaic photo for its reliability can also be maintained. Good design with good manufacturing will also increase the reliability of solar power plants, with the appropriate field-based design and appropriate installation procedures in the root analysis of the problem increase significant reliability.